Bioethical approach to re-constructive therapies. Treatment to change the homosexual orientation - Montoya Montoya, Gabriel Jaime (Acta Bioethica, 2006)
The interrelation between bioethics and gender studies is clear and contingent. It is obvious in the analysis of the re-constructive therapies for the "correction" or change of the homosexual orientation. This paper shows the fundamental elements which allow the bioethics dialogue about it in a summary way. Also, the fundamentals of the sexual orientation and their acknowledgement as a human right are exposed. Furthermore, some theoretical aspects are taken with respect to the use of physician power in the domesticating process. The paper finalizes analyzing some characteristics of the re-constructive therapies and showing the ethical arguments which refuse their application